Placevent: An algorithm for prediction of explicit solvent atom distribution-Application to HIV-1 protease and F-ATP synthase - Sindhikara, Daniel J.; Yoshida, Norio; Hirata, Fumio (Journal of computational chemistry, 2012)
We have created a simple algorithm for automatically predicting the explicit solvent atom distribution of biomolecules. The explicit distribution is coerced from the three‐dimensional (3D) continuous distribution resulting from a 3D reference interaction site model (3D‐RISM) calculation. This procedure predicts optimal location of solvent molecules and ions given a rigid biomolecular structure and the solvent composition. We show examples of predicting water molecules near the KNI‐272 bound form of HIV‐1 protease and predicting both sodium ions and water molecules near the rotor ring of F‐adenosine triphosphate (ATP) synthase. Our results give excellent agreement with experimental structure with an average prediction error of 0.39–0.65 Å. Further, unlike experimental methods, this method does not suffer from the partial occupancy limit. Our method can be performed directly on 3D‐RISM output within minutes. It is extremely useful for examining multiple specific solvent–solute interactions, as a convenient method for generating initial solvent structures for molecular dynamics calculations, and may assist in refinement of experimental structures. © 2012 Wiley Periodicals, Inc. We have created an algorithm for automatically predicting the explicit solvent atom distribution of biomolecules using 3D‐RISM. This procedure predicts optimal location of solvent molecules and ions given a rigid biomolecular structure and the solvent composition. Our results give excellent agreement with xperimental structure with an average prediction error of 0.39–0.65 Å. Our method can be performed directly on 3D‐RISM output within minutes.